Asymmetric monetary policy effects in Germany - Silke Tober; Vladimir N. Kuzin (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
In a small structural model we find asymmetries in the effects of monetary policy in Germany depending on whether the economy is in an upswing or a downswing. These two different regimes are also identified using a Markov-switching model and the Kalman filter. Our results indicate that the effects of monetary policy are significantly higher in a downswing than in an upswing. It follows not only that monetary policy has to raise interest rates markedly if an economy is overheating but also that once a downturn is discernible, interest rates have to be lowered rapidly so as to prevent an overly large reaction of the real economy.
Keywords: E44; E5; E32; C32; C51; 330; Asymmetry; monetary policy; Markov switching; structural model; Geldpolitik; Konjunktur; Schätzung; Deutschland; Markov switching